Theoretical and Methodological Aspects of the Economic and Environmental Efficiency Valuation of Solid Household Waste Recycling Теоретико-методические аспекты оценки экономико-экологической эффективности рециклинга твердых бытовых отходов - Dovga Tatyana N. (Bìznes Inform, 2013)
The basic organizational and methodological problems of the economic and environmental efficiency valuation of solid household waste recycling that can arise in waste processing plants and complexes of Ukraine are investigated in the article. The urgency of implementing solid household waste recycling process was justified. The new approach to the classification of the economic and environmental efficiency valuation indicators of solid household waste recycling in Ukraine was proposed by the author. В статье исследованы основные организационно-методические проблемы оценки экономико-экологической эффективности рециклинга бытовых отходов, возникающих на мусороперерабатывающих заводах и комплексах Украины. Обоснована актуальность внедрения процесса рециклинга ТБО и предложено собственный подход к классификации показателей оценки эколого-экономической эффективности рециклинга бытовых отходов в Украине.